Association between postpartum systemic inflammation and serum calcium in healthy multiparous dairy cows: An exploratory observational analysis - R. Couto Serrenho; R.C. Neves; S.J. LeBlanc (JDS Communications, 2025)
Our objective was to investigate the association between serum total Ca concentration (tCa) and indicators of systemic inflammation (SI) in postpartum dairy cows. We hypothesized that the tCa-SI association varies in the first 8 d of lactation. This exploratory analysis used data from a field trial in which cows were randomly assigned to receive oral Ca supplementation after calving (OSCa), or not. Healthy multiparous cows (total n = 101; n OSCa = 51) from 2 farms in Ontario, Canada, were included. The inflammatory markers assessed were serum concentrations of albumin (a negative acute phase protein), and the positive acute phase proteins haptoglobin and serum amyloid A (SAA). Albumin, haptoglobin, and tCa were assessed at 0 (<12 h after calving), 0.5 (12 h), 1, 2, 4, 6, and 8 d after parturition; SAA was assessed at d 0, 2, and 4. Linear regression models were fitted while accounting for time as a repeated measure for each analyte, and included tCa, tCa2, days postpartum, parity (2 vs. ≥3), OSCa, the interactions of tCa × day postpartum, tCa2 × day postpartum, tCa × parity, tCa2 × parity, and farm as a random effect. A stepwise backward elimination approach was applied to improve model parsimony. The lowest albumin and greatest haptoglobin and SAA concentrations were observed at d 2. The association of albumin with tCa varied quadratically over time. At d 0, 0.5, 1, and 2, as tCa decreased, albumin increased, but at d 4, 6, and 8 as tCa decreased, albumin also decreased. At d 0, 0.5, and 1, when tCa <1.7 mmol/L, tCa and haptoglobin were positively associated. Total calcium <1.7 mmol/L was not observed ≥d 2. After d 1, cows with lower tCa tended to have greater haptoglobin concentrations. The greatest concentration of SAA occurred when tCa was 1.9 mmol/L. Values of tCa <1.9 mmol/L were mainly observed at d 0. At d 0, and when tCa was <1.9 mmol/L, lower tCa was associated with lesser SAA concentration. However, when tCa was >1.9 mmol/L (93% and 99% of the values observed at d 2 and 4, respectively), lower tCa was associated with greater SAA concentration. The associations between tCa and markers of SI changed in the first 8 d of lactation in clinically healthy cows. Potential interventions to modulate hypocalcemia or SI, or both, should consider their interactions. Future studies should further explore the association of the degree and duration of hypocalcemia and SI to better understand the direction and mechanisms of this relationship.